The hormonal response to stress is not modified by the dramatic decrease in prolactin plasma concentration during surgery for microprolactinoma. Issue 4 (1st October 1998) - Guieu, R; Dufour, H; Devaux, C; Brue, T; Rosso, J P; Grisoli, F; Grino, M; Enjalbert, A; Begoud, D; Broder, N; Rochat, H; Jaquet, P
Abstract : OBJECTIIVES: To determine the endocrine response to surgical stress in a homogeneous population of 36 women with microprolactinomas, particularly to evaluate the effect of the sharp decrease in plasma prolactin on stress induced hormonal secretion. In addition, the effects of exogenous opiates on prolactin secretion were studied. METHODS: The plasma kinetics of cortisol, prolactin, ACTH, GH, and β-endorphin like immunoreactivity (β-ELI) were analysed by including patients operated on with strict anaesthetic and surgical protocols, and by sampling blood every 10 minutes, starting at premedication up to 3 hours after induction. RESULTS AND CONCLUSION S : ( a ) Surgical stress or opiate administration did not induce prolactin release in patients with microprolactinoma. ( b ) The dramatic decrease in prolactin concentrations have apparently no effect on the release of other hormones involved in stress. ( c ) The existence of an early GH peak, independently of any surgical procedure, strongly suggests that GH is released by surgical stress whereas β-endorphin is secreted in response to pain. Thus GH may be a useful marker of surgical stress.